NATIONALISM AS A CONTEMPORARY MENACE: READING TAGORE’S THE HOME AND THE WORLD AS A COSMOPOLITAN TEXT - Jamshed, Mohammad (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
As the calls for global peace and peaceful coexistence grow louder, nationalism, often tearing apart the oldest and largest democracies, emerges as one of the formidable menaces to mankind today. It is a resurgent force in major democracies across continents. In Asia and particularly in the Indian subcontinent, it emerges in response to the colonial hegemony and the emulation of Western values. But it soon assumes a religious dimension. Tagore, in its rise as a global phenomenon, sees a threat to global peace and fraternity, an onslaught on human dignity, and calls it a 'destructive enthusiasm,' an 'epidemic of evil,' an edifice of illusions, and moral annihilation. Against the background of fragile peace and shattered human existence. This study investigates how nationalism dehumanizes people, kills a human character, distorts perceptions, divests them of moral ideals, reduces a man's life to a mechanical existence, and releases a demon of ethnonationalist violence by using text analysis as its research method. The study shows how the author's cosmopolitan vision is capable of guiding mankind in these troubled times. Besides, it shows how his vision can help people overcome this mass delusion and foster global understanding and peaceful coexistence.